Implementasi Fitur Question Answering pada Aplikasi Qur’an Berbasis Mobile Menggunakan Framework Flutter - Aldri Permana, Lutfi; Nazruddin Safaat H; Lestari Handayani; Muhammad Affandes (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
The divine commandments contained in the Muslim holy book, the Qur'an, are not only instructions and guidance, but also contain wisdom and deep meaning for mankind. This study aims to develop the Qur'an Question-Answer (QA) feature in the Flutter-based mobile Qur'an application as an innovative solution to facilitate understanding of the teachings of the Qur'an. By combining the advantages of Flutter technology in the construction of responsive user interfaces, this application is designed to provide natural language questions in understanding the contents of the Qur'an as well as facilitating the dissemination of religious messages in sharing the verses of the Qur'an. Application development uses the Rapid Application Development (RAD) method, as well as application testing using the Black Box Testing and User Acceptance Test (UAT) methods and the results obtained that the application is feasible to use.